2016
DOI: 10.1590/0103-8478cr20160255
|View full text |Cite
|
Sign up to set email alerts
|

Ancillary techniques on the evaluation of canine cutaneous mast cell tumors from Brazil

Abstract: The use of histologic classification by a 2-tier grading system only, immunohistochemistry (IHC) for KIT and Ki-67 and polymerase chain reaction (PCR) for internal tandem duplications (ITD) on exon 11 has improved the prognostication of canine cutaneous mast cell tumors (CCMTs) particularly in the United RESUMO O uso de classificação histológica por um novo sistema de graduação que utiliza apenas duas categorias, imuno-histoquímica (IHQ) para KIT e Ki-67 e reação de polimerase em cadeia (PCR) para mutações (du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Pattern III immunostaining was not observed in the present study. The vast majority of low grade neoplasms presented immunostaining pattern II, corroborating with the literature (Webster et al 2007, Fonseca-Alves et al 2015, Flores et al 2016, Sledge et al 2016. This information is important considering that it has been observed that MCTs that lose membrane expression and acquire cytoplasmic expression for KIT antigen, present a more aggressive biological behavior (Kiupel et al 2004).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Pattern III immunostaining was not observed in the present study. The vast majority of low grade neoplasms presented immunostaining pattern II, corroborating with the literature (Webster et al 2007, Fonseca-Alves et al 2015, Flores et al 2016, Sledge et al 2016. This information is important considering that it has been observed that MCTs that lose membrane expression and acquire cytoplasmic expression for KIT antigen, present a more aggressive biological behavior (Kiupel et al 2004).…”
Section: Discussionsupporting
confidence: 83%
“…That was the motivation for our prospective study, which sought to assess whether fixation time could be influencing the results of our retrospective study. Flores et al (2016), using other samples from the same laboratory (LPV-UFSM), observed positive immunostaining for Ki67 protein in approximately 70% of the samples analyzed. The difference in the percentage of immunostaining between this study and that by Flores et al (2016), even with different samples, could be associated with the systems of amplification (using a specific polymer for tissues of dogs and cats) and antigen retrieval (under controlled conditions of temperature and pressure) they used for Ki67 protein.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations